2011
DOI: 10.1002/nur.20425
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality and psychological well‐being: Testing a theory of family interdependence among family caregivers and their elders

Abstract: The family spirituality-psychological well-being model was developed and tested to explore how spirituality influences psychological well-being among elders and caregivers in the context of Korean family caregiving. The sample consisted of 157 Korean elder-family caregiver dyads in Seoul, Korea. The intraclass correlation coefficient and the actor-partner interdependence statistical model were used to analyze the data. There were significant correlations between elders' and caregivers' spirituality and between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 56 publications
2
32
0
2
Order By: Relevance
“…Ocorre a demanda de cuidados para auxílio nas atividades básicas de vida diária (colaboração na higiene pessoal, locomoção e alimentação) ou em atividades instrumentais (ajuda para realizar compras, ir ao médico, administrar recursos financeiros e proporcionar lazer), 9,12,23,[34][35][36][37][38][39][40] e o papel do cuidador no processo de recuperação de seu ente. 10,[34][35][36][37] Estes assumem uma jornada de mais de oito horas de cuidados sem o apoio de uma segunda pessoa, e ainda têm as atribuições domésticas de limpeza e responsabilidades com demais membros da família e, por vezes, trabalho extra.…”
Section: 31-33unclassified
See 1 more Smart Citation
“…Ocorre a demanda de cuidados para auxílio nas atividades básicas de vida diária (colaboração na higiene pessoal, locomoção e alimentação) ou em atividades instrumentais (ajuda para realizar compras, ir ao médico, administrar recursos financeiros e proporcionar lazer), 9,12,23,[34][35][36][37][38][39][40] e o papel do cuidador no processo de recuperação de seu ente. 10,[34][35][36][37] Estes assumem uma jornada de mais de oito horas de cuidados sem o apoio de uma segunda pessoa, e ainda têm as atribuições domésticas de limpeza e responsabilidades com demais membros da família e, por vezes, trabalho extra.…”
Section: 31-33unclassified
“…Ocorre a demanda de cuidados para auxílio nas atividades básicas de vida diária (colaboração na higiene pessoal, locomoção e alimentação) ou em atividades instrumentais (ajuda para realizar compras, ir ao médico, administrar recursos financeiros e proporcionar lazer), 9,12,23,[34][35][36][37][38][39][40] e o papel do cuidador no processo de recuperação de seu ente. 10,[34][35][36][37] Estes assumem uma jornada de mais de oito horas de cuidados sem o apoio de uma segunda pessoa, e ainda têm as atribuições domésticas de limpeza e responsabilidades com demais membros da família e, por vezes, trabalho extra. 9,41 Essa rotina diária de cuidados é gradativamente citada como geradora de tensão nos cuidadores, com recorrência da falta de conhecimento; a insegurança e o medo de como prosseguirá com os cuidados no domicílio; da privação da vida social; da interrupção ou adiamento de seus projetos de vida; do desejo, dependência e/ou obrigação de partilhar e acompanhar todos os cuidados; pela falta de recursos financeiros; do conflito familiar na tomada de decisão de quem será o cuidador; na indecisão em institucionalizar ou não; a apreensão quanto ao estado de saúde do ente; a preocupação com os demais membros, com seu emprego e com as novas adaptações requeridas.…”
Section: 31-33unclassified
“…Little is known about Korean elders' experience of spirituality and its relationship to health or well-being in Korean culture. A few investigators have reported that spirituality among Korean older adults is positively related to acceptance of death, satisfaction with life, positive and negative affect, depression, subjective well-being, and physical health such as physical function, and health promoting behaviors (Jang & Kim, 2003;Kim et al, 2011;Lee;Lee & Oh, 2003). However, these studies used the Spiritual Well-Being Scale developed by Paloutzian and Ellison (1982), which confounds measures of emotional wellbeing with spirituality (Koenig, 2008).…”
Section: Translation and Psychometric Testing Of The Korean Versions mentioning
confidence: 99%
“…Six bilingual translators with a bicultural background in Korean and English including 3 nursing professors, 1 linguistic professor, and 2 nurses participated in the translation procedure. Permission to use and to translate the SPS and the STS into Korean was obtained from Dr. Reed prior to the study (Kim et al, 2011).…”
Section: )Stagei:translationandexpertreviewmentioning
confidence: 99%
See 1 more Smart Citation